2022
DOI: 10.1186/s12916-022-02655-z
|View full text |Cite
|
Sign up to set email alerts
|

Identifying susceptibility of children and adolescents to the Omicron variant (B.1.1.529)

Abstract: Background The Omicron variant (B.1.1.529) is estimated to be more transmissible than previous strains of SARS-CoV-2 especially among children, potentially resulting in croup which is a characteristic disease in children. Current coronavirus disease 2019 (COVID-19) cases among children might be higher because (i) school-aged children have higher contact rates and (ii) the COVID-19 vaccination strategy prioritizes the elderly in most countries. However, there have been no reports confirming the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 28 publications
(18 reference statements)
0
19
0
Order By: Relevance
“…South Korea uses aggressive testing and thus has very low rates of underascertainment, as corroborated also by limited seroprevalence data. 10 Therefore, we assumed the true number of infections is 1.25-times the number of documented cases for each age stratum. BA.1 and BA.2 variants dominated until summer 2022 and BA.2 was gradually replaced by BA.5 and some BA.2.75 and XBB variants later in the year.…”
Section: Modelling Of China On Hong Kong and South Korea Omicron Wavesmentioning
confidence: 99%
“…South Korea uses aggressive testing and thus has very low rates of underascertainment, as corroborated also by limited seroprevalence data. 10 Therefore, we assumed the true number of infections is 1.25-times the number of documented cases for each age stratum. BA.1 and BA.2 variants dominated until summer 2022 and BA.2 was gradually replaced by BA.5 and some BA.2.75 and XBB variants later in the year.…”
Section: Modelling Of China On Hong Kong and South Korea Omicron Wavesmentioning
confidence: 99%
“…By December 27, 2022 there were 31,882 deaths and 28,772,196 confirmed infections. South Korea uses aggressive testing and thus has very low rates of under-ascertainment, as corroborated also by limited seroprevalence data (10). Therefore, we assumed the true number of infections is 1.25-times the number of documented cases for each age stratum.…”
Section: Modeling Of China On Hong Kong and South Korea Omicron Wavesmentioning
confidence: 99%
“…In the main analysis scenario, we used 45% of the non-elderly population being infected by summer and fatality impact reduced by half in the elderly strata. Both Hong Kong and South Korea had approximately 45% of their population infected in the respective time frame in their Omicron waves (6,10).…”
Section: Calculation Of China Covid-19 Deaths From Age-stratified Ifr...mentioning
confidence: 99%
“…This suggested that younger kids can transmit the Omicron variant infection at a higher rate, but have less severe clinical outcomes. Among these kids, those belonging to the age group of 0–2 years had a higher monthly incidence rate of COVID-19 as compared to those of 3–4 years of age during the emergence of the Omicron variant [ 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%